Innovative Approaches in Tourism Development to Revitalize Global Sustainability - Bayuningsih, Dewi; Dzulkifli, Muhammad; Muksin, Muksin (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2024)
Sustainable tourism has become a pivotal component in the pursuit of global sustainability, intertwining environmental, economic, and sociocultural dimensions to promote holistic development. This paper aims to revitalize the goal of global sustainability through innovative tourism practices, providing an in-depth analysis of successful case studies, emerging trends, and policy implications. Drawing on extensive literature and real-world examples, including notable initiatives in Indonesia, the study highlights the transformative potential of sustainable tourism. Key areas of focus include eco-tourism, community-based tourism, and smart tourism technologies, showcasing how these approaches contribute to environmental conservation, economic development, and cultural preservation. The discussion also addresses the challenges faced in policy implementation and offers strategic recommendations for stakeholders, including governments, industry professionals, and local communities. By integrating theoretical frameworks and practical insights, this paper provides a comprehensive roadmap for advancing sustainable tourism as a catalyst for global sustainability. The findings highlight the importance of collaborative efforts and continuous innovation to achieve the United Nations' Sustainable Development Goals (SDGs) through tourism.